Russian Culture and Theatrical Performance in America 1891-1933 - Pagani, Maria Pia (Mimesis Journal, 2024)
Maria Pia Pagani invites to read Valleri J. Hohman, Russian Culture and Theatrical Performance in America 1891-1933, Palgrave MacMillan, Palgrave Studies in Theatre and Performance History, New York 2011, pp. 230. Riferimento: Valleri J. Hohman, Russian Culture and Theatrical Performance in America 1891-1933, Palgrave MacMillan, Palgrave Studies in Theatre and Performance History, New York 2011, pp. 230.